2018
DOI: 10.1186/s12896-018-0444-z
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulose integration to 1G-ethanol process using filamentous fungi: fermentation prospects of edible strain of Neurospora intermedia

Abstract: BackgroundIntegration of first- and second-generation ethanol processes is one among the alternate approaches that efficiently address the current socio-economic issues of the bioethanol sector. Edible filamentous fungus capable of utilizing pentoses from lignocelluloses and also possessing biomass application as potential animal feed component was used as the fermentation strain for the integration model. This study presents various fermentation aspects of using edible filamentous fungi in the integrated firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…N. intermedia has been reported to grow in both filament and pellet forms in previous studies [71,74]. pH was reported to be a significant factor in the pellet formation of N. intermedia, where a pH of 3.5-4 resulted in the formation of pellets with a smooth outer surface [71].…”
Section: Morphologymentioning
confidence: 95%
“…N. intermedia has been reported to grow in both filament and pellet forms in previous studies [71,74]. pH was reported to be a significant factor in the pellet formation of N. intermedia, where a pH of 3.5-4 resulted in the formation of pellets with a smooth outer surface [71].…”
Section: Morphologymentioning
confidence: 95%
“…However, it has not been widely explored for submerged cultivation of filamentous fungi. One example includes the work carried out by Nair et al [70] during a research approach for integration of substrates used for production of first-and second-generation ethanol, namely sidestreams from ethanol production from starch and lignocellulosic materials, respectively. The proposed strategy would avoid the supplementation of the cultivation medium with costly nutrients that might also entail an environmental footprint.…”
Section: Filamentous Fungal Cultivation Processmentioning
confidence: 99%
“…Ethanol yields ranging from 0.18 to 0.46 g/g have been documented for strains of Fusarium oxysporum, one of the best fungal producers of ethanol [21]. Nair et al [18] reported an ethanol yield of 0.23 g/g for Neurospora intermedia in a mixture of dilute acid pretreated and enzymatically hydrolyzed wheat straw and thin stillage from the first-generation ethanol process. A more recent study, targeting direct fermentation of lignocellulosic biomass using a mixed consortium of fungi, has shown ethanol yields of 0.037, 0.40, and 0.41 g/g for the fungi Bjerkandera adusta, Fomitopsis palustris, and Schizophyllum commune, respectively, while using glucose as the carbon source [7].…”
Section: Evaluation Of the Growth Of B Fulva During Oxygen-limited Phasementioning
confidence: 99%
“…The ability to sustain growth and survive under anaerobic conditions, and the tolerance of these fungi to ethanol which they produce under anaerobic conditions have been relatively understudied and so is their potential to directly produce ethanol from lignocellulosic biomass. Recent studies have indicated the potential of using edible filamentous fungi for valorization of spent liquors and C5-rich streams from grain and lignocellulosic biorefineries where edible fungal protein is generated along with ethanol fermentation [17,18]. Apparently, most fungi are capable of utilizing cellulose and hemicellulose-derived sugars, but their ability to synthesize lignocellulolytic enzymes varies.…”
Section: Introductionmentioning
confidence: 99%